Aetiology, Clinical Presentation and Outcome of Patients with Ascites in Medicine Unit of Chittagong Medical College Hospital : A Study of 100 Cases (IAHS Medical Journal, 2022)
Background: Ascites is a common clinical condition encountered by physician in day-to-day practice. It will be an understatement to state that ascites is common in our country rather it is safe to say that ascites is one of the most common mode of presentation in the hospital wards in our country. The aim of the study was to find out the common causes of ascites by evaluating the clinical presentations along with the ascitic fluid study and other routine and related investigations followed by observing the short-term outcome of the patients with ascites during their hospital tenure.Materials and methods: It is a descriptive observational study carried out in Medicine Department of Chittagong Medical College Hospital (CMCH) over a period of one year (October 2008- September 2009). Hundred consecutive adult patients admitted in different units of Medicine Department, CMCH with ascites were the subjects of this study. After selection of cases detailed clinical history was taken and elaborate physical examination was done. Common criteria for data collection were followed in every case. Ascitic fluid was collected and examined in all 100 cases. Selected investigations were designed considering the symptomatology and systems affected and reserved for those cases where symptoms and signs were strongly in favour of the diagnosis that needs to be investigated accordingly. All the data were computed and analysed with proper statistical methods.Results: Data analysis of the present study reveals that Cirrhosis of liver is the commonest cause of ascites (50%). Next two major causes are Tubercular Peritonitis (21%) and Congestive Cardiac Failure (14%). Other important causes include hepatocellular carcinoma (7%) Su-bacute Hepatic Failure (3%) Intra-abdominal malignancy (Except hepatocellular Carcinoma) (3%) and Nephrotic Syndrome (1%). Clinical presentations have shown that most of the patients had multiple and variable presentations. Serum ALP, AST, ALT, Ascitic Fluid Total Protein (AFTP) (F=5.04, p=0.0009